2016
DOI: 10.18632/oncotarget.14285
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL receptor gene editing unveils TRAIL-R1 as a master player of apoptosis induced by TRAIL and ER stress

Abstract: TRAIL induces selective tumor cell death through TRAIL-R1 and TRAIL-R2. Despite the fact that these receptors share high structural homologies, induction of apoptosis upon ER stress, cell autonomous motility and invasion have solely been described to occur through TRAIL-R2. Using the TALEN gene-editing approach, we show that TRAIL-R1 can also induce apoptosis during unresolved unfolded protein response (UPR). Likewise, TRAIL-R1 was found to co-immunoprecipitate with FADD and caspase-8 during ER stress. Its def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 30 publications
4
87
0
Order By: Relevance
“…Moreover, the specificity and the selectivity of NVs were assessed in HCT116 cells deficient for DR4 and DR5 (Dufour et al, ) (HCT116–DKO). In agreement with their selectivity towards TRAIL signaling and their lack of toxicity, neither NV10 nor NV100, even at high concentration (10 μg · mL −1 ), inhibited the viability of HCT116–DKO cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the specificity and the selectivity of NVs were assessed in HCT116 cells deficient for DR4 and DR5 (Dufour et al, ) (HCT116–DKO). In agreement with their selectivity towards TRAIL signaling and their lack of toxicity, neither NV10 nor NV100, even at high concentration (10 μg · mL −1 ), inhibited the viability of HCT116–DKO cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor‐related apoptosis‐inducing ligand receptor‐deficient HCT116 (DKO) cells were generated by the TALEN approach, described by Dufour et al ().…”
Section: Methodsmentioning
confidence: 99%
“…24 Simultaneously, pro-caspase 8 binds to FADD and is activated as a result of dimer formation, which in turn, triggers activation of proteolytic cleavage effector caspases like caspase 3 that digest cellular proteins to induce apoptosis. 25 In our in vitro study, we found that the levels of DR4, DR5 and cleaved caspase 3 in pPB-SSL-TRAIL group were significantly higher than those in the groups treated with free rhTRAIL or SSL-TRAIL. The encapsulation of TRAIL in pPB-SSL delivery system did not seem to change how TRAIL functions, but rather made it easier for more TRAIL molecules to target aHSCs at their receptors.…”
Section: Discussionmentioning
confidence: 59%
“…Our work proposes to combine both static numeric methods (docking simulation) and dynamic simulations in order to accelerate the crea- between the TRAIL-based nanovector and DR4. 38 Comparatively, DR5 is able to trigger cell motility, invasion, and metastasis, but in a less pronounced way than DR4. 11,39 So far, it should be noted that authors generally hypothesized that DR5 plays a more important role than DR4 in triggering apoptosis in cells expressing both receptors.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this corresponds to the first evidence of such stability in a theoretical study. On the basis of recent findings, DR4 is the only true agonist receptor of TRAIL and could explain such complex stability between the TRAIL‐based nanovector and DR4 . Comparatively, DR5 is able to trigger cell motility, invasion, and metastasis, but in a less pronounced way than DR4 .…”
Section: Resultsmentioning
confidence: 99%